Manajemen dalam Pengembangan Media di Observatorium Ilmu Falak Universitas Muhammadiyah Sumatera Utara - Hidayat, Muhammad (UMSU, 2024)
Management in Media Development is very necessary because Management can function in building creativity and innovation of administrators in an organization. The data collection method and technique in this research is qualitative research with a case study approach. Management in Media Development at OIF UMSU is carried out by implementing four management functions (planning, organizing, mobilizing and supervising). In terms of planning, OIF UMSU as a research and service institution must have a roadmap in both the short and long term. In the event that OIF UMSU organizes groupings, the arrangement and distribution of members' duties is described and stated in the job description document. Then in terms of Mobilization, Leaders can provide breakthroughs and in terms of Supervision, the Supervision carried out is not only in the form of punishment for those who make mistakes but also in the form of appreciation for achievements.